Regional development as a chain process of organizational dynamics and technological routes: the case of Santa Catarina's Western Region - Aléssio, Bianca Cristina (2014)
The last decades witnessed a transformation of the concept of development and of the analysis of its explanatory variables. Regional/local specificities became important aspects of development processes since each territory reacts differently to different strategies and creates specific solutions for its development. This article analyzes the path of a regional development process from the perspective of the institutional, schumpeterian and territorial approach theories. They provide important references to analyze development processes at the local level, as they consider history, culture, behavior codes, values and techniques as determinants of development. The study builds on Santa Catarina's Western region case and shows that regional development processes can be analyzed with the support of these theories as a chain of organizational dynamics and local technological trajectories that influence each other and determine the possible courses of territorial development.